Cha o 3, a cypress pollen allergen, does not activate basophils in Japanese cypress pollinosis - Yoshiaki Kobayashi, MD; Keisuke Suzuki, MSc; Minoru Tateno, PhD; Yuki Nakamura, PhD; Kayoko Ishimaru; Yuka Nagasaka; Daiju Sakurai, MD, PhD; Katsuyo Ohashi-Doi, PhD; Atsuhito Nakao, MD, PhD (Journal of Allergy and Clinical Immunology: Global, 2024)
Background: In Japan, pollinosis caused by the Japanese cypress (JCy) Chamaecyparis obtusa is among the very common seasonal allergies. In JCy pollinosis, Cha o 1 is the first major allergen, and Cha o 2 is the second major allergen. Recently, Cha o 3 was identified as a new JCy pollen allergen in JCy pollinosis. However, the relative contribution of Cha o 3 to JCy pollinosis compared with that of Cha o 1 and that of Cha o 2 has not been fully elucidated. Objective: This study aimed to clarify the allergenicity of Cha o 3 compared with that of Cha o 1 and Cha o 2 in JCy pollinosis. Methods: We recruited 27 patients with JCy pollinosis and performed the basophil activation test (BAT) with native (n) Cha o 1, Cha o 2, and Cha o 3 purified from JCy pollen. In addition, we a performed JCy-specific IgE suppression test. Results: In the BAT, 26 of 27 patients (96%) and 18 of 27 patients (67%) showed positive basophil activation in response to n Cha o 1 and n Cha o 2, respectively, as judged by CD203c expression. Little CD203c expression in response to n Cha o 3 was seen. The presence of n Cha o 3 marginally reduced the titer levels of JCy-specific IgE. Conclusion: Cha o 3 showed little ability to activate basophils and suppress JCy-specific IgE titers compared with Cha o 1 or Cha o 2 in patients with JCy pollinosis. Thus, Cha o 3 may not be a major allergen in JCy pollinosis.